Analysis and design of control system for desktop size concrete 3D printer - Iqbal, A. R.; Muhammad, Khairul Fikri (Penerbit UMP, 2022)
Concrete, in construction, structural material consisting of a hard, chemically inert particulate substance, known as aggregate (usually sand and gravel), that is bonded together by cement and water. Concrete is the world's second-most-used substance after water, and it is also the most extensively used building material. 3D printer has become a prominent method of additive manufacturing with its rapid prototyping capabilities and is able to reduce the time and cost of any complex manufacturing process. This paper describes work the process of 3D design, analysis, manufacturing and testing of a concrete 3D printer to explore the plausibility and sustainability of concrete 3D printing to replace the conventional construction method. A desktop size concrete 3D printer concrete 3D printer with 0.5×0.5×0.5 m print volume is developed for lab testing, which utilizes computer-based control system to layer-by- layer construct physical objects is developed to study the usability of the printer as well as the feasibility of replacing the conventional construction method. The development of the 3D printer is divided into two parts, Part A: Mechanical and Part B: Control System. Concrete 3D printing technology is not widely known and is expensive to be deployed. Thus, greater research and development of the technology is required to evolve into a more mature study that is accessible to consumers. The project output envisions as to lay a foundation for extended studies and applications of 3D printed concrete in Malaysia